Mediating dangerously : the frontiers of conflict resolution - Cloke, Ken, 1941- (Jossey-Bass, 2001)
Sometimes it's necessary to push beyond the usual limits of the mediation process to achieve deeper and more lasting change. Mediating Dangerously shows how to reach beyond technical and traditional intervention to the outer edges and dark places of dispute resolution, where risk taking is essential and fundamental change is the desired result.